2019
DOI: 10.14740/jocmr3713
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Troponin I Elevation on Duration of Mechanical Ventilation and Length of Intensive Care Unit Stay in Patients With Sepsis

Abstract: BackgroundSepsis is a leading cause of mortality and morbidity. Recent studies suggest that troponin elevation is associated with increased mortality in sepsis patients. The purpose of this study is to determine the effect of troponin elevation on mechanical ventilation duration and intensive care unit (ICU) length of stay in patients with sepsis. Additionally, we investigated the association between troponin elevation and septic shock.MethodsThe study is a retrospective observational cohort study, conducted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…We found that myocardial injury is an independent risk factor for weaning failure from mechanical ventilation [25]. Abdalla et al also demonstrated that troponin elevation was associated with a longer duration of mechanical ventilation in patients who were admitted to the ICU with sepsis [22].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…We found that myocardial injury is an independent risk factor for weaning failure from mechanical ventilation [25]. Abdalla et al also demonstrated that troponin elevation was associated with a longer duration of mechanical ventilation in patients who were admitted to the ICU with sepsis [22].…”
Section: Discussionsupporting
confidence: 57%
“…Myocardial injury may be caused by hypoperfusion, hypoxia, global ischaemia, surgery, and sepsis in noncardiac patients. Previous studies showed that myocardial injury was associated with mortality among patients undergoing noncardiac surgery [16,[22][23][24]. A prospective cohort study recruited 21,842 patients who underwent noncardiac surgery at 23 centres in 13 countries.…”
Section: Discussionmentioning
confidence: 99%
“…We found that myocardial injury is an independent risk factor for weaning failure from mechanical ventilation [ 29 ]. Abdalla et al also demonstrated that troponin elevation was associated with a longer duration of mechanical ventilation in patients who were admitted to the ICU with sepsis [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review included nine studies involving 719 patients who suffer from pre-eclampsia and concluded that in such pre-eclampsia pregnant women cardiac troponin I might be elevated [26]. Previous studies also showed that myocardial injury was associated with mortality among patients undergoing noncardiac surgery [17,27,28]. Our previous study retrospectively enrolled 381 critically ill patients who underwent major abdominal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[3,15,16] We found that troponin I elevation was associated significantly with increased 30-day and one-year mortality. Moreover, Mohammed et al [17] reported that troponin I elevation was associated with prolonged mechanical ventilation. Differences among studies are attributable to the inclusion of only patients with severe sepsis and septic shock in previous studies, whereas our study population comprised all patients admitted to the non-cardiac ICU with various medical and surgical conditions.…”
Section: Discussionmentioning
confidence: 99%